Canopy interactions and physical stress gradients in subtidal communities. (14th May 2015) - Bennett, Scott; Wernberg, Thomas; de Bettignies, Thibaut; Kendrick, Gary A.; Anderson, Robert J.; Bolton, John J.; Rodgers, Kirsten L.; Shears, Nick T.; Leclerc, Jean‐Charles; Lévêque, Laurent; Davoult, Dominique; Christie, Hartvig C.; et al.
Abstract Species interactions are integral drivers of community structure and can change from competitive to facilitative with increasing environmental stress. In subtidal marine ecosystems, however, interactions along physical stress gradients have seldom been tested. We observed seaweed canopy interactions across depth and latitudinal gradients to test whether light and temperature stress structured interaction patterns. We also quantified interspecific and intraspecific interactions among nine subtidal canopy seaweed species across three continents to examine the general nature of interactions in subtidal systems under low consumer pressure. We reveal that positive and neutral interactions are widespread throughout global seaweed communities and the nature of interactions can change from competitive to facilitative with increasing light stress in shallow marine systems. These findings provide support for the stress gradient hypothesis within subtidal seaweed communities and highlight the importance of canopy interactions for the maintenance of subtidal marine habitats experiencing environmental stress.